Brief Report: Expression of Interferon‐γ Receptor Genes in Peripheral Blood Mononuclear Cells Is Associated With Rheumatoid Arthritis and Its Radiographic Severity in African Americans. Issue 5 (May 2015) - Tang, Qi; Danila, Maria I.; Cui, Xiangqin; Parks, Lauren; Baker, Brandi J.; Reynolds, Richard J.; Raman, Chander; Wanseck, Keith C.; Redden, David T.; Johnson, Martin R.; CLEAR Investigators; Bridges, S. Louis
<x xml:space="preserve">Abstract</x> Objective The factors responsible for radiographic severity in African American patients with rheumatoid arthritis (RA) are poorly understood. We sought to identify genes whose expression in peripheral blood mononuclear cells is associated with radiographic severity in RA. Methods In the first phase of the study, we performed real‐time quantitative polymerase chain reaction to analyze the expression of 182 candidate genes in 40 African American RA patients with extremes of radiographic damage (low versus high radiographic scores) and disease duration (≤2 years versus >2 years) and 20 healthy African American control subjects; the genes were selected based on plausible immune pathways. In the second phase, we analyzed the expression of the genes that were shown to be significantly associated with radiographic scores in 576 African American patients with RA and 51 African American control subjects who had not been studied previously, accounting for autoantibody status and disease duration. Results We observed significant differences in IFNGR1 expression between patients with RA and control subjects (adjusted P [Padj] = 6 × 10−14) and in IFNGR2 expression between RA patients with erosions and those with no erosions (Padj = 0.01 by Wilcoxon's rank sum test). We also observed significant correlations between IFNGR2 expression and radiographic scores (Padj = 0.03 for erosions, Padj = 0.04 for joint space narrowing, and Padj = 0.03 for total radiographic score [zero‐inflated negative binomial regression model]) and annualized progression rate (Padj = 0.0024 by Spearman's correlation analysis). Conclusion These findings have important implications with respect to the role of interferon‐γ (IFNγ) in the pathogenesis of RA and may lead to identification of a biomarker for radiographic damage. Additional studies are needed to define the cell subsets responsible for the association of IFNγ receptor gene expression with radiographic findings, which downstream mechanisms are involved, and generalizability to other RA populations.